The relationship between maternal employment and stunting among 6–59 months old children in Gurage Zone Southern Nation Nationality People’s region, Ethiopia: A comparative cross-sectional study - Ahmed, Mekiya; Zepre, Kebebush; Lentero, Kifle; Gebremariam, Tigist; Jemal, Zeyneba; Wondimu, Asegedech; Bedewi, Jemal; Melis, Tamirat; Gebremeskel, Alazar (Frontiers in Nutrition, 2022)
background: Stunting is among the major public health problem, according to the Ethiopian mini demographic and health survey, the prevalence of stunting among under-five children was 37%, in addition, stunting has a trans-generational effect on a mother’s nutritional status. However, evidence on the causal contribution of maternal employment to stunting among under-five children is not well understood in Ethiopia. This study aimed to compare stunting status and associated factors among under-five children of employed and unemployed mothers, Gurage zone, Southern Ethiopia, 2021. Methods: A community-based comparative cross-sectional study was conducted among 671(330 employed and 341 unemployed) randomly selected mother-child pairs in Gurage Zone, Southern Ethiopia. A pretested semi-structured tool and validated anthropometric measurements were used to collect the data. The data were entered into Epi data version 3.1 and exported to Statistical package of social science (PSS ) version 23.0 for analysis. Results: In this study a total of 671 mother–child pair (330 (94.6%) employed and 341(97.7%) unemployed) were participated with total response rate of 96%. Among the total participants about 70(21.2%)[95% CI (17, 25.5)] and 98(28.8%)[95% CI (23, 33.4)] of children’s of employed and unemployed mothers respectively were stunted . Mothers level of education primary and secondary[AOR=1.79, 95% CI: (0.8, 3.7), age between 25-29 years[AOR=0.08, 95% CI: (0.006, 0.904)], monthly family income >5000 birr [AOR=0.042, 95% CI:(0.00, 00.64)]and child age between 6-23 month [AOR=2.9; 95% CI (1.48, 5.8)] were predictors of stunting among children of employed mothers Whereas mothers not having nutritional education [AOR=2.5; 95% CI (1.1, 5.6)], monthly family income < 2,000 ETB [AOR=2.64; 95% CI (1.34, 5.19)] sex of child (female) [AOR=2.3; 95% CI (1.3, 3.8)and mothers educational status of read and write only [AOR= 2.9, 95% CI: (1.4, 5.8)]were predictors of stunting among child of unemployed mothers. Conclusion: In our study prevalence of stunting is observed slightly lower compared to the regional, national, and WHO cut-off point of 40% set for stunting. Maternal education, maternal age, family income, child age, and frequency of breastfeeding were significantly associated with stunting among children of employed mothers.